Preparation and encapsulation mechanism study of oxyresveratrol by β-cyclodextrin and hydroxypropyl-β-cyclodextrin - He, Jianfei (fi=Turun yliopisto|en=University of Turku|, 2018)
The encapsulation mechanism of oxyresveratrol and β-cyclodextrin (β-CD) as well as hydroxypropyl-β-cyclodextrin (HP-β-CD) was studied in this research. As this research shown, oxyresveratrol and two cyclodextrins (CDs) were able to form inclusion complexes in a 1:1 stoichiometry. However, the interaction with HP-β-CD was more efficient, showing up as higher encapsulation constant (KF) (35864.72 ± 3415.89 M-1). The KF values exhibited a strong dependence on temperature and pH, which decreased as them increased. From the thermodynamic parameters (ΔHo, ΔSo, and ΔGo) of the oxyresveratrol loaded β-CD (oxyresveratrol-β-CD) and HP-β-CD (oxyresveratrol-HP-β-CD), it could be inferred that the complexation process was spontaneous and exothermic, and the main driving forces between oxyrsveratrol and CDs were hydrogen bonding as well as van der waals force. Besides, molecular docking combined with 1H NMR were used to explain the most possible mode of interactions between oxyresveratrol and CDs. Moreover, based on the optimal formulation, 207.19 ± 0.57 mg and 198.30 ± 2.25 mg of oxyresveratrol was included in 1.00 g of the oxyresveratrol-β-CD and oxyresveratrol-HP-β-CD dried powder with the water solubility up to 14.44 ± 0.83 mg/mL and 47.33 ± 0.78 mg/mL, yielding about 32 and 106-fold increase in oxyresveratrol solubility (about 0.4 mg/mL), respectively. The physical stability and dissolution rate study showed that the formation of inclusion complexes significant enhanced the storage stability of oxyresveratrol and its dissolution rate. These results indicated that β-CD and HP-β-CD may be suitable delivery systems of oxyresveratrol. Furthermore, as illustrated in this study, inclusion complexes exhibited strong antibrowning effects on fresh apple juice in 24 hours, showing its great potential application in the food industry.